2013
DOI: 10.1016/j.pain.2013.04.035
|View full text |Cite
|
Sign up to set email alerts
|

A phase III placebo- and oxycodone-controlled study of tanezumab in adults with osteoarthritis pain of the hip or knee

Abstract: Tanezumab is a humanized monoclonal antinerve growth factor antibody in development for treatment of chronic pain. In a phase III, placebo- and active-controlled study, we investigated the efficacy and safety of tanezumab for osteoarthritis (OA) hip or knee pain. Patients (N=610) received up to 2 doses of intravenous tanezumab (5 or 10mg in 8-week intervals), controlled-release oral oxycodone (10 to 40 mg every 12 hours), or placebo. The primary endpoint was mean change from baseline to week 8 in Western Ontar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
138
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(146 citation statements)
references
References 32 publications
5
138
1
2
Order By: Relevance
“…Currently, there are no approved biological therapies for patients with OA. Recent studies showed significant improvement in pain and function of knee OA with tanezumab; however, it should be mentioned that mild to moderate AEs occurred [32][33][34][35].…”
Section: Tanezumabmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, there are no approved biological therapies for patients with OA. Recent studies showed significant improvement in pain and function of knee OA with tanezumab; however, it should be mentioned that mild to moderate AEs occurred [32][33][34][35].…”
Section: Tanezumabmentioning
confidence: 99%
“…During the neonatal period, NGF supports development of the sensory neurons; in adults, NGF is essential in raising awareness of the nociceptor function of neurons with the onset of pain and hyperalgesia in chronic pain. This function may be observed after injury and inflammation, when NGF expression ultimately increases, including in patients with OA, who also express high levels of NGF in their joints [32][33][34][35].…”
Section: Tanezumabmentioning
confidence: 99%
See 1 more Smart Citation
“…Однако проведенные исследования, к сожале-нию, обнаружили и ряд недостатков танезумаба, кото-рые в итоге приостановили его регистрацию и начало применения в реальной практике. Оказалось, что новое лекарство вызывает серьезные НР -появление сенсор-ных симптомов (парестезия и гипестезия), в ряде случа-ев появление или ухудшение полиневропатии, а также ускорение прогрессирования ОА, которое в отдельных случаях потребовало проведения эндопротезирования [61][62][63].…”
Section: глюкокортикоидыunclassified
“…Но в этих работах выявлен и ряд недостатков танезумаба, что в итоге приостановило его регистрацию и начало применения в реальной практике. Это серьезные НР: появление сенсор-ных симптомов (парестезия и гипестезия), в некоторых слу-чаях развитие полиневропатии, а также ускорение прогрес-сирования ОА, которое у отдельных пациентов потребовало выполнения эндопротезирования [35][36][37].…”
Section: %unclassified